Peranan Guru Aqidah dalam Menanamkan Nilai-nilai Keagamaan pada Siswa Kelas VII A MTs Ta'mirul Islam Surakarta Tahun Ajaran 2014-2015 - Setyawan, Haris Budi, Dr. Abdullah Aly, M.Ag, Maria Ulfa, S.Pd.I (2015)
ABSTRACT TEACHER role in imparting VALUE aqidah-RELIGIOUS VALUES IN CLASS VII A MTs ISLAMIC TA'MIRUL Surakarta Doctrine YEAR 2014-2015 Haris Budi Setiawan, G000130172, Department of Islamic Education (MT) Faculty of Islamic Studies, University of Muhammadiyah Surakarta. It is the goal of research husband FOR knowing Religious Values ​​That Ditanamkah IN Grade VII A MTs Ta'mirul Surakarta Islamic hearts and Role of Teachers Aqeedah MataPelajaranAqidah hearts Religious Instill Values ​​ON Grade VII A MTs Surakarta Islamic Ta'mirul Academic Year 2014 -2015. Operational research is qualitative research methods Field WITH THE Sources of primary data and secondary data taken Namely Yang Resources Directly from principals, teachers aqidah, and Grade VII A MTs Ta'mirul Islam Surakarta. Initial data collection techniques using interviews, observation and documentation. While data analysis technique used is the deductive method, ie a way of thinking Still Being Who Where research tool since choosing, finding a problem Building hypothesis, and conduct field observations Until WITH Test data. Research conducted taxable income, author obtained the findings that the Model Curriculum The KMI Ta'mirul implemented in Islam refers To Curriculum MONE and MORA plus Curriculum Content Curriculum lembaga.Adapun religious ASPECTS Values ​​The ditanamkah IN Grade VII A MTs Ta'mirul Surakarta Islamic Aqeedah hearts eye Lessons include 3 ASPECT principal, ie: To Allah ATTITUDE, ATTITUDE To Humans, And ATTITUDE To Nature. While the role of the teacher aqidah hearts instill religious values ​​IN Grade VII A MTs Year Ta'mirul Surakarta Islamic teachings lay BETWEEN 2014-2015: Always socialize and evaluate the level of achievement for understanding Students Back Against Lessons aqidah, trying to integrate the Islamic religion Values ​​KE Student Self hearts, develop teaching materials WITH ALL bernuansakan Islam, fostering congregational prayer, and muwajahah. Atmosphere Interaction between teachers and students learning at MTs hearts Surakarta Islamic Ta'mirul built WITH democratic atmosphere Basic differences affection And Relationships And togetherness in which teachers position Himself as the figure of teachers, friends, and parents. Keywords: Role of teachers aqidah, value-nilaikeagamaan, Students.